Diseño bidimensional reflejado en los símbolos iconográficos de las máscaras de madera aplicado en el área textil de la comunidad del Quilotoa de la provincia de Cotopaxi. - Quindil Choloquinga, Ivan José (2023)
The research project that is presented below, is developed in the Quilotoa community in the province of Cotopaxi, canton of Latacunga, the investigative team finds a problem, which is of the utmost importance to solve through thorough investigation. This begins the investigative process that focuses on the wooden masks of the Quilotoa community that are made by hand in the same, since they represent a tourist attraction, but are not recognized in their entirety as are different beads. that they carry out there, therefore, the investigative team presents a proposition, which is called "Two-dimensional design reflected in the iconographic symbols of the wooden masks applied in the textile area in the Quilotoa community of the Cotopaxi province". The investigation is carried out with the purpose of contributing to the revaluation of the local culture, tradition of the Province and of course the Country, through the use of the appropriate tools and knowledge acquired during the course of the Graphic Design career. To start with the research, the same research techniques are used that allow data to be collected in a better way, such as interviews and surveys, which help to ensure the feasibility of the information and thus support the current project, being already applied, it can be known more thoroughly that although there is research about the paintings, and different beads that are made there, there is no research about the origin, production or meaning of the wooden masks of the Quilotoa community, allowing the topic addressed to be completely viable. The information collected is scarce, however, it is obtained to fill the gaps that are presented or that the proposed topic had, therefore, the little discernment of what are the crafts that are manufactured in this community is better highlighted. The final product that is obtained are the application designs based on the graphic proposals of the concept of the modules of the wooden masks of the Quilotoa community, taking as reference the most representative ones, without losing their originality of the object of study, for their preparation, the project methodology is applied, with which a novel, unusual design is achieved with its own identity.